Predicting playing status in junior Australian Football using physical and anthropometric parameters. Issue 2 (March 2015) - Woods, Carl T.E.; Raynor, Annette J.; Bruce, Lyndell; McDonald, Zane; Collier, Neil
Abstract: Objectives: To use physical and anthropometric parameters to predict playing status in junior Australian Football. Design: Cross-sectional observational. Methods: Participants were recruited from the under 18 competition within the West Australian Football League and classified into two groups; elite (state representative; n  = 50; 17.9 ± 0.5 y; 184.8 ± 6.9 cm; 80.6 ± 9.4 kg) and sub-elite (non-state representative; n  = 50; 17.8 ± 0.6 y; 179.8 ± 5.4 cm; 74.4 ± 7.9 kg). Both groups completed physical/anthropometric tests inclusive of a 5 m, 10 m and 20 m sprint, an agility test, stationary vertical jump, dynamic dominant and non-dominant foot vertical jump, 20 m multistage fitness test, standing height and body mass. A multivariate analysis of variance was used to test the main effect of 'status' on the physical/anthropometric parameters, whilst logistic regression models were used to predict playing status using the physical/anthropometric parameters. Results: On average, the elite group were taller, heavier, had a greater stationary vertical jump, dynamic dominant and non-dominant foot vertical jump and higher maximal aerobic capacity as measured by the multistage fitness test ( p  < 0.05). The combination of standing height, dynamic vertical jump non-dominant foot and the 20 m multistage fitness test were the strongest predictors of status (Akaike's Information Criterion = 96.35). Conclusions: Despite mean differences in a number of parameters, the combination of standing height, dynamic vertical jump non-dominant foot and the multistage fitness test were the strongest predictors of status and thus important tests for initially identifying potential talent in junior Australian Football.